PENERAPAN MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) UNTUK MENINGKATKAN AKTIVITAS DAN KEMANDIRIAN BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI MIA 2 SMA ISLAM AS-SHOFA PEKANBARU - Nuzuriah, Nuzuriah; Erna, Maria; Yasmi, Elva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This is a classroom action research. This research is an attempt to improve student learning activities in chemistry and independence on class XI MIA 2 SMA Islam As-Shofa Pekanbaru by using learning model auditory intellectually repetition. Student learning activity which is repaired the activity of listening to teacher’s explanation, propose the question, submit answers or opinions, group discussion, and do a task the teacher gives. Student learning independence which is repaired to read the source of the literature independently, dare to express opinions, do their own evaluation and be unyielding in completing the evaluation. This research consisted of two cycles. Each cycle consisted of two meetings that went through four stages of implementation: planning, action, observation, and reflection. The collecting data used observation and test. The analysis data was describ with descriptively by using percentage technique. Based on the results obtained, it can be concluded the using of learning model auditory intellectually repetition can improve the activity and independence of student learning. It can be seen by the improvement of student’s learning activity from 52,5% at the first cycle to 70% at the second cycle, and learning independences from 51,25% at the first cycle to 64,87% at the second cycle.Keyword : Learning model auditory intellectually repetition, activities, learning independence